Modelling Local and Regional Economic Development in Turkey: A Curate's Egg - Aksel Ersoy (European Regional Science Association (ERSA), 2012)
This paper explores and unpacks the nature of the processes shaping regional economic growth in Turkey using an econometric modelling strategy. Economic modelling is an important approach to the analysis and understanding of regional growth and development. Over the decades, there have been a range of attempts to measure and understand the dynamics of regional growth through the modelling of underlying internal and external forces. However, existing empirical research in this field has focussed on regions in economically advanced and technologically innovative economies and comparable studies of less developed and emerging countries and their regions that suffer from poverty, unemployment and regional disparities are far fewer. As a consequence, the broader picture of the dynamics of regional development in less developed countries, particularly its social and political origins and the overall changes in regional inequality, have remained elusive and less clear. However, as globalization deepens and processes such as Europeanization and regionalization facilitate and accelerate the implementation of externally developed policies, less developed and emerging economies have started to adopt the `successful' regional economic planning policies and practices developed and implemented in totally different national contexts. The problem with this issue is that those policy ideas have only partial relevance in the developed country context potentially making them even less relevant in developing economies. To explore this problem, this paper seeks to understand, empirically, the drivers of local and regional development in Turkey and how they can be used to develop a theoretically informed econometric analysis in the context of an emerging market economy. Not only has this form of analysis not been undertaken in Turkey, but the theories of local and regional economic development have had a major impact on the Turkish regional planning process. A set of econometric models is developed to explore the validity of a range of theoretical propositions in explaining the trajectories of regional economic change in Turkey between 2004 and 2008. Growth is calibrated in terms of employment and changing rates of unemployment in the chosen time period in the eighty one provinces of Turkey. The results of the study explain that implications of the current local and regional economic development theories are a Curate's Egg – good in parts – because these theories are only partially relevant in the Turkish context.
Keywords: 330; R10 Abstract contentRegional growth; emerging economies; Turkey